Sodium humate modified superabsorbent resin with higher salt‐tolerating and moisture‐resisting capacities. Issue 48 (9th September 2018) - Guan, H.L.; Yong, D.L.; Fan, M.X.; Yu, X.L.; Wang, Z.; Liu, J.J.; Li, J.B.
ABSTRACT: The superabsorbent resin (SAR) containing sodium humate (SH) has been synthesized by free‐radical graft copolymerization with acrylic acid, 2‐acrylamido‐2‐methylpropane sulfonic acid, and SH as monomers in aqueous solution, using N, N ′‐methylenebisacrylamide as crosslinking reagent and potassium persulfate as initiator. The structure and morphology of the as‐prepared SARs were fully characterized by Fourier transform infrared, scanning electron microscopy and thermogravimetric analysis, respectively. Meanwhile, the effects of crosslinking reagent, initiator, SH, and neutralization degree on the water absorbency of SAR were studied. The results showed that the adding of SH in the SAR enhanced the salt‐tolerating and moisture‐resisting capacities obviously. The SAR without SH [poly(acrylic acid) (PAA)/2‐acrylamido‐2‐methyl‐1‐propanesulfonic (AMPS)] showed a maximum water absorbency of 600 g g −1 in distilled water and 60 g g −1 in 0.9 wt % NaCl solution, while SAR modified by SH (PAA/AMPS/SH) exhibited the maximum water absorbency of 1380 g g −1 in distilled water and 117 g g −1 in 0.9 wt % NaCl solution. Furthermore, the moisture‐resisting capacity of PAA/AMPS/SH decreases to 8 wt % compared with PAA/AMPS. PAA/AMPS/SH also has better water absorbency in different cation solutions. The results indicated that the introduction of SH could enhance the performance of SAR obviously. The possible reasons with this enhancement were also investigated. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46892. Abstract : The porous sodium humate modified superabsorbent resin (SAR) shows better properties including water absorbency, moisture‐resisting, and salt‐tolerating capacities than bare SAR.